Prevalence and determinants of maternal near miss in Ethiopia: a systematic review and meta-analysis, 2023 - Befkad Derese Tilahun; Mulat Ayele; Gebremeskel Kibret Abebe; Addis Wondmagegn Alamaw; Biruk Beletew Abate; Alemu Birara Zemariam; Gizachew Yilak (Systematic Reviews)
Abstract Background Ethiopia’s progress in maternal health is commendable, but the persistence of life-threatening complications during pregnancy and childbirth highlights the need for further research and action. While individual studies on maternal near-misses (MNM) exist, a comprehensive understanding of their prevalence and underlying factors remains elusive. This systematic review and meta-analysis aimed to bridge that gap by consolidating available evidence, paving the way for targeted interventions to improve maternal health outcomes. Methods A search for relevant studies was performed using the databases of PubMed, Scopus, the Cochrane Library, and Google Scholar, from years November 26 to 30, 2023, encompassed studies conducted in Ethiopia and published in English that reported the prevalence of maternal near miss and/or identified at least one determinant. Duplicate studies were removed using Endnote X8, resulting in a total of 13 studies included for analysis. The methodological quality of the included studies was assessed using the Joanna Briggs Institute’s (JBI) quality appraisal checklist. The data synthesis and statistical analysis were performed using STATA Version 17 software. The pooled prevalence was presented using forest plots based on the random effects model. Result The nationwide combined prevalence of maternal near misses (MNM) in Ethiopia was an adjusted odds ratio (AOR) of 12.9 and a 95% confidence interval (CI) of 6.30 to 19.49. Several factors were identified as determinants of maternal near-misses based on the pooled estimate. These factors included the absence of formal education (AOR = 2.48, 95% CI: 1.59–3.36), pre-existing chronic conditions (AOR = 4.70, 95% CI: 2.97–6.42), lack of antenatal care (AOR = 3.09, 95% CI: 2.12, 4.05), previous cesarean section (AOR = 4.40, 95% CI: 3.51, 5.28), and a history of referral (AOR = 2.67, 95% CI: 1.36–3.98); thus, factors were found to contribute significantly. Conclusion Maternal near-misses are prevalent in Ethiopia, with determinates including chronic conditions, lack of education, referral history, inadequate antenatal care, and previous cesarean sections. Addressing this requires improving women’s education access, enhancing antenatal care services for early complication management, and proactive chronic condition care during pregnancy. Promoting safe delivery practices, reducing unnecessary cesarean sections, and enhancing referral systems are crucial steps. Effective implementation necessitates collaboration among healthcare providers, policymakers, the Ethiopian Ministry of Health, and hospitals to reduce maternal near-misses in Ethiopia. The cross-sectional design hinders drawing causal conclusions, and the relevance of the findings may be limited to countries with specific socio-economic and cultural contexts, considering that the research was conducted exclusively in Ethiopia. Systematic review registration PROSPERO CRD42023485844.